Use of phytotoxic rice crop residues for weed management - Pheng, Sophea; Olofsdotter, Maria; Jahn, Gary; Adkins, Steve (Wiley, 2010)
There is a general perception among Cambodian rice (Oryza sativa) farmers that, after harvesting, rice crop residues that are incorporated into the field benefit the growth of the subsequent rice crop. However, the effect of this action upon weed establishment and growth has not yet been considered. A series of pot and field trials were conducted to determine whether such action could inhibit weed establishment and/or growth. The pot studies first evaluated the response of the test plant (rice line ST‐3) and three weed species, barnyardgrass (Echinochloa crus‐galli), small umbrella sedge (Cyperus difformis), and water primrose (Ludwigia octovalves), to the residue of 16 rice lines and the field trials were later conducted to evaluate the response of the same test plants to the residue of seven putatively allelopathic rice lines and one non‐allelopathic rice line. The residue of all the studied rice lines, depending on how long they had been incorporated into the soil, reduced the establishment and growth of all three weed species, as well as the rice crop. However, if the residue's incorporation was delayed by 2 weeks or only a proportion of the residue was incorporated, the rice crop could withstand the growth‐inhibiting effect, while the inhibition of the establishment and growth of the three weed species was retained. These responses of rice and the weeds to rice crop residues might provide a basis for a weed management strategy, particularly in the resource‐poor rice‐production systems of Cambodia.